ANALYSIS OF THE VALUE OF THE TEPUK TEPUNG TAWAR TRADITION IN TRADITIONAL WEDDING CEREMONIES IN LINGGA REGENCY: Analisis Nilai Tradisi Tepuk Tepung Tawar pada Upacara Adat Pernikahan Kabupaten Lingga - Julia julia; Dody Irawan; Ahada Wahyusari; Suhardi; Legi elfitra; Abdul Malik (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the traditional values ​​embodied in the "puking bumbu tawar" traditional ceremony at weddings in Lingga Regency. Data were obtained through observation, in-depth interviews with traditional leaders and cultural figures, and documentation of ceremonial activities. The results show that the "puking bumbu tawar" tradition possesses a deeply meaningful sign system, based on Charles Morris's semiotic theory, which consists of signs, signals, and symbols. This tradition is a form of cultural expression passed down from generation to generation and plays a crucial role in shaping the social, spiritual, and moral order of society. The "puking bumbu tawar" tradition plays a crucial role in maintaining the continuity of Malay cultural values, strengthening social relations, and strengthening regional identity. "puking bumbu tawar" serves not only as a traditional ritual but also as a medium for transmitting cultural values, a means of character education, and strengthening the identity of the Lingga Malay community amidst the tide of modernization.